Concentration-Dependent Bimodal Effect of Specific 18 kDa Translocator Protein (TSPO) Ligands on Cell Death Processes Induced by Ammonium Chloride: Potential Implications for Neuropathological Effects Due to Hyperammonemia - Caballero, Beatriz; Veenman, Leo; Bode, Julia; Leschiner, Svetlana; Gavish, Moshe (CNS & Neurological Disorders - Drug Targets, 2014)
The role of the 18-kDa Translocator Protein (TSPO) in cell death induced by NH4Cl (1-50 mM) for 24-72 hours to human glioblastoma U118MG cells was investigated. Cell death was already observed after 48 hours of treatment with NH4Cl at 5 mM. Dose and time-responses curves indicated that 15 mM of NH4Cl applied for 72 hours was the optimal condition for our viability assays. For example, 72 hours of 15 mM of NH4Cl caused a 50.3% increase in propidium iodide uptake, and lactate dehydrogenase release was 41.2% of the positive control, indicating significant increases in cell death. Furthermore, compared to vehicle control, these experimental conditions resulted in a significant decrease of 44.9% of the mitochondrial activity, a 62.3% increase in incidence of collapse of mitochondrial membrane potential, and an increase of 49.0% of cardiolipin peroxidation. In addition, a significant 4.3 fold increase in the maximal binding capacity (Bmax) of TSPO was found in NH4Cl-exposed cells. Surprisingly, western blot analysis and real-time PCR did not demonstrate changes in TSPO expression. We also found that neither NH4Cl nor glutamine (a metabolic product of enhanced NH4Cl levels) inhibited binding of the TSPO ligand [3H]PK 11195. Interestingly, we observed a bimodal effect of the TSPO ligands PK 11195, Ro5-4864, and FGIN-1-27 on the toxicity of NH4Cl; such that 1-100 nM concentrations of TSPO ligands were protective, while concentrations above 1 μM enhanced NH4Cl-induced cell death processes. In conclusion, TSPO takes part in a bimodal way in the lethal effects induced by NH4Cl in glial type cells.
Keywords: 18 kDa Translocator Protein (TSPO)